“Startup”: Bisnis Kuliner Rintisan di Masa Pandemi Covid-19 - Aulya Ika Pratiwi (Universitas Muslim Maros, 2021)
Pandemic of Covid-19 has impacted on almost all aspects of life, including the field of economic. This is due to a government policy to work from home (WFH) and to study from home which causes changes in people's daily routines. One of the activities that generate money in the midst of the pandemic of Covid-19 is by starting an online culinary business that is intertwined with government policies related to preventing the transmission of Covid-19. This research was conducted in the city of Makassar, the capital city of South Sulawesi, as one of the areas with the highest rate of cases infected by Covid-19, and as a city known for its culinary. There were ten informants who participated in this study, who are varied on the basis of age (between 21 and 23 years), sex (eight women and two men), status (seven of whom were college students, two fresh graduates and an entrepreneur), position (owners, managers, employees). How they manage this startup culinary business is depended on the management and this is the key to running it. There are four aspects deals with this management, namely the marketing concept, the division of labor, the profit-sharing system, and how the time is divided between education, main work and the startup culinary business. To market their products in this startup culinary business, the strategies used include the use of technology, consistency of product quality (such as ingredients and taste)/services (such as attitudes towards consumers), and promotions to attract consumers (such as promotion of savings packages, Friday 'at blessing, free shipping, discounted prices, holding a give a way).